2022
DOI: 10.1001/jamaoto.2022.0684
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Topical Antisepsis and Surgical Site Infection in Patients Undergoing Upper Aerodigestive Tract Reconstruction

Abstract: IMPORTANCE Surgical site infections (SSIs) after vascularized reconstruction of the upper aerodigestive tract (UADT) are associated with considerable morbidity. The association between perioperative prophylaxis practices, particularly topical antisepsis, and SSIs remains uncertain.OBJECTIVE To assess the association between perioperative topical antisepsis and SSIs in patients undergoing vascularized reconstruction of the UADT. DESIGN, SETTING, AND PARTICIPANTSThis cohort study included patients from 12 academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Aneesh Karir, M.D. 4 In a prospective study of more than 500 patients undergoing upper aerodigestive tract surgery with complex flap reconstruction, the authors found that patients could have their risk of surgical site infection reduced by 51 percent with the use of a preoperative topical antisepsis mucosal preparation. The response to piperacillin and tazobactam was a 58 percent decrease in the infection rate.…”
mentioning
confidence: 99%
“…Aneesh Karir, M.D. 4 In a prospective study of more than 500 patients undergoing upper aerodigestive tract surgery with complex flap reconstruction, the authors found that patients could have their risk of surgical site infection reduced by 51 percent with the use of a preoperative topical antisepsis mucosal preparation. The response to piperacillin and tazobactam was a 58 percent decrease in the infection rate.…”
mentioning
confidence: 99%